2019
DOI: 10.1097/mlr.0000000000001047
|View full text |Cite|
|
Sign up to set email alerts
|

Functional Status Is Associated With 30-Day Potentially Preventable Readmissions Following Home Health Care

Abstract: Background: Beginning in 2019, home health agencies’ rates of potentially preventable hospital readmissions over the 30 days following discharge will be publicly reported. Objectives: Our primary objective was to determine the association between patients’ functional status at discharge from home health care and 30-day potentially preventable readmissions. A secondary objective was to identify the most common conditions resulting in potentially preventable readmissions. Design: Retrospective cohort study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 12 publications
2
21
0
Order By: Relevance
“…Respiratory infection was also found to be a major cause of readmission in our study population, which was consistent with previous findings 6,7,11 . Severe cognitive impairment is a risk factor of dysphagia that can lead to aspiration pneumonia 42,43 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Respiratory infection was also found to be a major cause of readmission in our study population, which was consistent with previous findings 6,7,11 . Severe cognitive impairment is a risk factor of dysphagia that can lead to aspiration pneumonia 42,43 .…”
Section: Discussionsupporting
confidence: 92%
“…To inform and improve the development of preventive strategies, it is important to consider the possible mechanisms through which later‐stage cognitive impairment increases the risk of PAR. Our finding that congestive heart failure is one of the most common reasons for PAR was consistent with previous studies conducted in the United States and Japan 6,8,11 . Moreover, heart failure is a target condition for the Centers for Medicare & Medicaid Services Hospital Readmissions Reduction Program 35 .…”
Section: Discussionsupporting
confidence: 91%
“… 4 , 5 , 6 , 7 , 8 Studies have identified an inverse association between functional status and risk of hospital readmission. 9 , 10 , 11 , 12 In addition, there is a growing body of literature on the detrimental effects of acute care hospitalization on functional independence. 13 , 14 , 15 , 16 Loyd et al 14 reported that 30% of adults aged 65 years and older who were hospitalized in medical-surgical acute care experienced hospital-associated disability, defined as loss of independence in activities of daily living (ADLs) following acute hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that the presence of pain was one of the risk factors for rehospitalization among patients with HF (Kang et al, 2016;Madigan et al, 2012a). A number of studies have examined functional status among patients with HF during home healthcare as it is known to be associated with HF however none have explored the link between symptoms and functional status (Fergenbaum et al, 2015;Madigan et al, 2012b;McClintock et al, 2014;Middleton et al, 2019;Sezgin et al, 2017). Moreover, there is an absence of studies using OASIS data that have examined the relationship between pain and functional status among HF patients.…”
Section: Introductionmentioning
confidence: 99%